Microtearing mode (MTM) turbulence in JIPPT-IIU tokamak plasmas. (27th March 2015) - Hamada, Y.; Watari, T.; Nishizawa, A.; Yamagishi, O.; Narihara, K.; Ida, K.; Kawasumi, Y.; Ido, T.; Kojima, M.; Toi, K.
Abstract: Magnetic, density and potential fluctuations up to 500 kHz at several spatial points have been observed in the core region of JIPPT-IIU tokamak plasmas using a heavy ion beam probe. The frequency spectra of the density and magnetic oscillations are found to be similar, whereas there are large differences in the phase, coherence and frequency dependences deduced from signals at adjacent sample volumes. These differences allow us to ascribe the detected magnetic fluctuations to the microtearing mode (MTM) by simple dispersion relations of the MTM in collisionless and intermediate regimes. The frequency-integrated level of magnetic fluctuations around 150 kHz (100–200 kHz) is, a level high enough for the ergodization of the magnetic surface and enhanced electron heat loss as derived by Rechester and Rosenbluth (1978 Phys. Rev. Lett. 40 38 ). This level is consistent with the measurements performed using cross-polarization scattering of microwaves in the Tore Supra tokamak. Our results are the first direct experimental verification of the MTM in the core region of tokamak plasmas, which has been recently observed in gyrokinetic simulations using a very fine mesh in tokamak and ST plasmas.